PENGARUH PENGUASAAN STRUKTUR KALIMAT TERHADAP KEMAMPUAN MENULIS EKSPOSISI PADA MURID KELAS V SEKOLAH DASAR INPRES TAMABONGONG - Ahmad Irsan; Muhammad Akhir (Universitas Pakuan, 2021)
THE EFFECT OF SENTENCE STRUCTURE MASTERING ON EXPOSITION WRITING ABILITY IN CLASS V ELEMENTARY SCHOOL STUDENTS TAMABONGONG INPRESThe purpose of the study was the effect of mastery of sentence structure on the ability to write exposition in fifth grade students of Inpres Tamabongong Elementary School. This type of research is quasi-experimental because in this study no specific treatment was given, but only revealed the symptoms that had existed when this research was conducted, so there was no direct control over the independent variables. The sample in quantitative research is part of the population in a study. The number of samples in this study were 15 students. Data collection methods used are learning outcomes tests and documentation. The data analysis technique used is the first by using a descriptive statistical approach and linear regression. The results showed that 1) The mastery of sentence structure was based on the results of the categorization of mastery of sentence structure in students, it was found that they were still in the category of scores of 14-20, scores of 26-30, and at scores of 14-20 whose mastery of sentence structure had not increased like the others. While in the posttest, 14 people were found to be moderate and there was 1 person whose mastery of sentence structure got better who was in the high category. 2) The results of data analysis obtained a probability value (p-value) of 0.042. Because the probability value (p-value) is less than 0.050, it means that the regression model in this study can be said that X (mastery of sentence structure) is dependent on Y (ability to write expository essays).